Association of poor sleep with multiple chronic conditions among adult residents in Beijing: a cross-sectional survey - Ying-qi WEI; Ai-juan MA; Jin XIE (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo analyze the relationship between poor sleep and multiple chronic conditions (MCC) among residents aged 18 - 79 years in Beijing in 2017 for providing reference to the prevention and control of chronic disease comorbidity. MethodsA total of 13 240 permanent residents aged 18 - 79 years were recruited from 16 districts of Beijing municipality with stratified multistage cluster sampling. Face-to-face questionnaire interviews, physical examination and laboratory detections were conducted among the residents during August - December 2017. Complex sampling weighting method was used to estimate the prevalence of poor sleep status and MCC and correlations between poor sleep status and MCC were analyzed with unconditional multivariate logistic regression models. ResultsAll the residents completed the survey. The self-reported prevalence rate of poor sleep status at least three days in a week during past 30 days was 25.8% (n = 3 413) for snoring / sleep apnea, 19.2% (n = 2 536) for difficulty in falling asleep, 23.4% (n = 3 103) for two and more times of intermediate awakening in one night, 20.2% (n = 2 671) for early awakening, and 2.8% (n = 367) for taking sleeping pills; the complex sampling weighted prevalence rate of poor sleep (reporting one or more bad sleep conditions) was 52.1% (n = 6 490). Totally 4 980 sufferers of MCC were identified among all the participants, with a weighted MCC prevalence rate of 41.7%. Unconditional multivariate logistic regression analysis revealed that the participants reporting the poor sleep status were associated with MCC, with the odds ratios (95% confidence intervals) of 1.955 (1.731 - 2.208) for the participants reporting snoring / sleep apnea, 1.914 (1.591 - 2.202) for intermediate awakening of ≥ two times, 1.802 (1.534 - 2.117) for early awakening, 1.625 (1.380 - 1.913) for difficulty in falling asleep, and 2.617 (1.907 - 3.592) for taking sleeping pills after adjusting for confounding factors such as gender, age, education, marital status, place of residence, smoking, alcohol drinking during past 7 days, physical activity, active physical examination and body weight. ConclusionPoor sleep status and MCC were prevalent and a variety of poor sleep conditions were related to MCC among 18 - 79 years old residents in Beijing.